Disaster readiness and risk reduction - Rimando, Rolly E.; Belen, Josefina G. (Rex Book Store, Inc., 2016)
"Keeping safe from natural hazards requires constant preparedness, even long before a potentially disastrous event happens. The most prepared are those armed with relevant information and understanding of hazards and disasters. Disaster Readiness and Reduction is intended for students as a textbook and as a reference for people from all walks of life who are threatened by natural hazards. Included in this book are numerous images and illustrations, activities, and examples that reflect the Philippine setting, experiences, and reality. While this book illustrates how science can be applied in adapting to natural hazards, it also teaches readers the effectiveness of a multidisciplinary approach in managing disasters. It also emphasizes the wisdom of a community-based method of disaster risk reduction and management"--Back Cover.